2007
DOI: 10.1002/j.2168-9830.2007.tb00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Considering Context: A Study of First‐Year Engineering Students

Abstract: High-quality engineering design requires an understanding of how the resulting engineered artifact interacts with society, the natural environment, and other aspects of context. This study examines how first-year engineering undergraduates approached two engineering design tasks. We focused on how much students considered contextual factors during problem-scoping, a critical part of the design process. As part of a larger, longitudinal study, we collected data from 160 students at four U.S. institutions. Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 32 publications
2
148
0
1
Order By: Relevance
“…For example, Kilgore et al (2007) studied students' behavior in two different design projects. They analyzed how strongly teams considered contextual factors in their decisions using both qualitative and quantitative tools.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kilgore et al (2007) studied students' behavior in two different design projects. They analyzed how strongly teams considered contextual factors in their decisions using both qualitative and quantitative tools.…”
Section: Data Collectionmentioning
confidence: 99%
“…Multiple experiences of PBL use to first-year engineering students can be found in the literature (Kilgore et al, 2007;Lima et al, 2012;Montero & Gonzalez, 2009;Palmer & Hall, 2011). This article describes four years of PBL application during the first semester of Industrial Engineering and points out the results and learning, year after year, as well as remaining challenges.…”
Section: Introductionmentioning
confidence: 99%
“…She further argues that such beliefs are developed in the course of the undergraduate engineering curriculum. Moreover, Kilgore et al's study found that beginning (and especially women) students were "sensitive to important contextual factors" (p. 321) 33 and further argue that "efforts to broaden participation in engineering should consider legitimizing and fostering context-oriented approaches to engineering earlier in the curriculum" (p. 321) 33 . Many other scholars discuss this tension between the social realities of traditional engineering practice and a lack of social awareness practicing engineering courses and among engineering students and professionals [34][35][36][37] .…”
Section: Literature Review: Social and Technical Dimensions Of Enginementioning
confidence: 99%
“…Three percent of those statements were coded jointly with the second coder as described before. The remaining 17% were coded independently and inter-rater agreement measured by computing Cohen's kappa coefficient, a commonly accepted method of assessing inter-coder reliability [29]- [31]. An agreement was defined as both coders assigning the same code to a transcript segment.…”
Section: Validitymentioning
confidence: 99%